The Development of PJOK Learning Devices Based on Local Wisdom and Technology Using the Teaching Games for Understanding (TGfU) Model to Improve Students’ Motor Skills - Dian Pujianto; Bayu Insanistyo; Abang Ismail (CV Media Inti Teknologi, 2026)
Purpose of Study: Physical Education, Sport and Health (PJOK) plays a vital role in developing students’ learning domains, namely their motor skills, physical fitness, cognitive abilities and social skills. However, in many educational settings, PJOK learning is still dominated by technique-oriented approaches that emphasize skill execution rather than understanding the tactical aspects of games. This study aims to develop a Physical Education, Sports, and Health (PJOK) learning device based on local wisdom and technology using the Teaching Games for Understanding (TGfU) design to improve students’ motor skills. Methodology: The Research and Development (R&D) method was adapted from the Borg and Gall development model, which was simplified into several stages, including preliminary study, product design, expert validation, product revision, and field testing. The participants involved two physical education experts and one PJOK teacher as a practitioner evaluator. The instruments used in this research consisted of validation questionnaires designed to assess the feasibility of the developed learning device in terms of learning material suitability, instructional design, clarity of learning steps, and practicality of implementation. Data were analyzed using descriptive statistics in percentage form. Main Finding: The results showed that the developed PJOK learning device achieved an expert validation score of 85%, categorized as very feasible, while practitioner evaluation results reached 75%, categorized as feasible for implementation in physical education learning. Novelty/Originality of This Study: The integration of local wisdom and technology into the TGfU model provides meaningful and contextual learning experiences for students. It not only enhances students’ engagement but also supports the development of motor skills and decision-making abilities in game situations.